IMPLEMENTASI KEBIJAKAN JALUR DOMISILI PADA SISTEM PENERIMAAN MURID BARU SEKOLAH MENENGAH PERTAMA DI SMPN 143 JAKARTA UTARA - Rafelia Ramadhania; Sri Suwitri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The New Student Admissions System (SPMB) in North Jakarta has used a zoning system as an effort to equalize access to education, bring students' residences closer to schools and eliminate the stigma of favorite schools. The implementation of this policy is based on Minister of Education and Culture Regulation Number 1 of 2021 and changed its name based on Minister of Education and Culture Regulation Number 3 of 2025 concerning the New Student Admission System, however there are still obstacles in the policy implementation process. The aim of this research is to analyze the implementation of the SPMB policy for the State Junior High School zoning system in North Jakarta and identify supporting and inhibiting factors for the implementation of this policy using the theory of public policy implementation according to Grindle and Van Meter and Van Horn. Data collection techniques were carried out using interviews, observation and literature studies through primary and secondary data sources as well as qualitative analysis. The results of this research show that policy implementation has been implemented but has not run optimally, as indicated by the existence of some people who choose schools based on the school's academic achievement, school reputation and school facilities. The supporting factors in implementing this policy are related to the policy targets, availability of resources, communication between organizations, characteristics of implementing agents and the attitudes of policy implementers. However, economic, social, and political conditions in the community and communication between organizations related to the manipulation of Family Card data so that the distribution of public school education is uneven & the lack of learning motivation of students who graduate through the domicile path with an older age than other paths. Researchers recommend optimizing socialization to the community, continuing efforts to improve education by the local government together with schools in facilitating facilities and infrastructure, human resources, and school management.